2018
DOI: 10.1038/s41401-018-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Annonaceous acetogenin mimic AA005 suppresses human colon cancer cell growth in vivo through downregulation of Mcl-1

Abstract: Annonaceous acetogenins are a well-established family of natural products with significant bioactivities, especially high cytotoxic and antitumor activities. AA005 is an annonaceous acetogenin mimic that has shown significant cytotoxicity against a variety of cancer cell lines, but its in vivo antitumor effects have not been demonstrated so far, and its anticancer mechanisms remain ambiguous. In this study, we investigated the effects of AA005 on human colon cancer cell lines in vivo. Human colon carcinoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…AA005 is an Annonaceous acetogenin mimic that inhibited tumor growth by promoting nuclear translocation of apoptosis-inducing factor (AIF) and inducing AIF-dependent cell death in vivo human colon cancer cell lines. In vivo SW620 (human colorectal cancer) and in vitro RKO (poorly differentiated colon carcinoma) cell lines revealed that treatment with AA005 showed down-regulation in Bcl 2 and Mcl-1 [ 55 ]. In silico research on acetogenins reverse ABCB1-mediated multidrug resistance in colon cancer: Annohexocin, Annomuricin, Annomuricin B, Annomuricin E, Annonacin A, Annonacin, Annonacin-10-one, Annonacinone, Annopentocin, Annopentocin B, Annopentocin C, Cis-corossolone, Corossolone SL, Epomuricenin A, Epomuricenin B, Gigantetrocin A, Gigantetronenin, Goniothalamicin, Muricapentocin, Muricatocin A, Muricatocin B, Muricoreacin, Solamin revealed that Annonacin, Annohexocin and Annomuricin showed the highest docking scores [ 56 ].…”
Section: Bioactive Metabolites Responsible For Various Pharmacologica...mentioning
confidence: 99%
“…AA005 is an Annonaceous acetogenin mimic that inhibited tumor growth by promoting nuclear translocation of apoptosis-inducing factor (AIF) and inducing AIF-dependent cell death in vivo human colon cancer cell lines. In vivo SW620 (human colorectal cancer) and in vitro RKO (poorly differentiated colon carcinoma) cell lines revealed that treatment with AA005 showed down-regulation in Bcl 2 and Mcl-1 [ 55 ]. In silico research on acetogenins reverse ABCB1-mediated multidrug resistance in colon cancer: Annohexocin, Annomuricin, Annomuricin B, Annomuricin E, Annonacin A, Annonacin, Annonacin-10-one, Annonacinone, Annopentocin, Annopentocin B, Annopentocin C, Cis-corossolone, Corossolone SL, Epomuricenin A, Epomuricenin B, Gigantetrocin A, Gigantetronenin, Goniothalamicin, Muricapentocin, Muricatocin A, Muricatocin B, Muricoreacin, Solamin revealed that Annonacin, Annohexocin and Annomuricin showed the highest docking scores [ 56 ].…”
Section: Bioactive Metabolites Responsible For Various Pharmacologica...mentioning
confidence: 99%
“…We then investigated the in vivo antitumor efficacy of AA005 in xenograft mice model. Based on the effective therapeutic dose of AA005 in SW620 tumor-bearing nude mice, [22] BALB/c mice bearing the commonly used mouse derived 4T1 xenografts were administered AA005 (0, 1 and 5 mg/kg/day, respectively) for 13 days via intraperitoneal injection. As shown in Figure 5A, administration of AA005 didn't influence the body weight of the mice compared to DMSO (control) treatment, indicating no obviously harmful side effect was caused by AA005.…”
Section: Aa005 Displays Antitumor Activity In Vivomentioning
confidence: 99%
“…Consequently, there is an urgent need to explore more safe and effective new compounds for the treatment of obesity, especially those compounds derived from or originating in nature plants. AA005, a recently-identified new annonaceous acetogenin mimic who demonstreated selective antitumor activity in vivo in our previous work [14][15][16][17][18][19] . Interestingly, recent studies have shown that crude leaf extracts from Annonaceae plants have potential anti-diabetes and antioxidant effects, which strongly prompted us to investigate other pharmacological activities of AA005 20 .…”
Section: Introductionmentioning
confidence: 97%
“…Our previous ndings suggested that high dose of AA005 suppressed human colon cancer cell growth in vivo mediated by apoptosis-inducing factor (AIF) and mitochondrial Complex I components 15,16 . Evidence from other studies showed that muscle-and liver-speci c AIF ablation in mice could counteract the development of insulin resistance, diabetes, and obesity 24 .…”
Section: Introductionmentioning
confidence: 99%